2016
DOI: 10.1371/journal.pone.0163571
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin C Intake Reduces the Risk of Type 2 Diabetes in Chinese Adults: HOMA-IR and T-AOC as Potential Mediators

Abstract: Despite growing interest in the protective role that dietary antioxidant vitamins may have in the development of type 2 diabetes (T2D), little epidemiological evidence is available in non-Western populations especially about the possible mediators underlying in this role. The present study aimed to investigate the association of vitamin C and vitamin E intakes with T2D risk in Chinese adults and examine the potential mediators. 178 incident T2D cases among 3483 participants in the Harbin People Health Study (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…32 Moreover the third pattern had high loadings for vitamin B 12 and retinol, which are both highly concentrated in foods of animal origin, and in particular in the liver. This pattern was characterized by a negative loading of vitamin C, which is known to be a marker of a diet rich in fruit and vegetables, which have previously been associated with a reduced risk of T2DM.…”
Section: Micronutrient Patterns and T2dm Riskmentioning
confidence: 98%
See 1 more Smart Citation
“…32 Moreover the third pattern had high loadings for vitamin B 12 and retinol, which are both highly concentrated in foods of animal origin, and in particular in the liver. This pattern was characterized by a negative loading of vitamin C, which is known to be a marker of a diet rich in fruit and vegetables, which have previously been associated with a reduced risk of T2DM.…”
Section: Micronutrient Patterns and T2dm Riskmentioning
confidence: 98%
“…This pattern was characterized by a negative loading of vitamin C, which is known to be a marker of a diet rich in fruit and vegetables, which have previously been associated with a reduced risk of T2DM. 32 Moreover the third pattern had high loadings for vitamin B 12 and retinol, which are both highly concentrated in foods of animal origin, and in particular in the liver. 30 The recommended intake for vitamin B 12 is 2.4 μg/day, whereas that for retinol is 700 μg/day; 23 in women above Q4 of the third pattern, the intake of vitamin B 12 and retinol was fiveand threefold higher, respectively.…”
Section: Micronutrient Patterns and T2dm Riskmentioning
confidence: 99%
“…Two prospective study cohorts were recruited in Harbin, the capital and largest city of Heilongjiang province in north China, to investigate the impacts of diet and nutrition on chronic non-communicable diseases. They were the Harbin People's Health Study (HPHS) [20,21] and the Harbin Cohort Study on Diet, Nutrition and Chronic Noncommunicable Diseases (HDNNCDS) (registered at http:// www.chictr.org.cn/showproj.aspx?proj=6833 as ChiCTR-ECH-12002721) [22]. Participants in the HPHS and the HDNNCDS were recruited in 2008 and 2010, and the first follow-up surveys were conducted in 2012 and 2015-2016, with an average of 4.2 and 5.3 years follow-up, respectively.…”
Section: Study Populationmentioning
confidence: 99%
“…However, recent studies have shown that micronutrients are also involved (4,5) . It has been found that fat-soluble vitamins with antioxidant effects, such as vitamins A and E, may have protective effects against oxidative stress-driven pathogenesis and complications of chronic diseases including type 2 diabetes (5)(6)(7)(8)(9) . Moreover, interests have also been shown (5,(10)(11)(12)(13)(14) in the possible roles of the other two fat-soluble vitamins, vitamins K and D.…”
mentioning
confidence: 99%